Screening and Identification of Prognostic Tumor-Infiltrating Immune Cells and Genes of Endometrioid Endometrial Adenocarcinoma: Based on The Cancer Genome Atlas Database and Bioinformatics - Chen, Bingnan; Wang, Di; Li, Jiapo; Hou, Yue; Qiao, Chong (Frontiers in Oncology, 2020)
Background: Endometrioid endometrial adenocarcinoma (EEA) is one of the most common tumors in the female reproductive system. With the further understanding of immune regulation mechanism in tumor microenvironment, immunotherapy is emerging in tumor treatment. However, there are few systematic studies on EEA immune infiltration. Methods: In this study prognostic tumor-infiltrating immune cells (TIICs) and related genes of EEA were comprehensively analyzed for the first time through the bioinformatics method with CIBERSORT algorithm as the core. Gene expression profile data were downloaded from the TCGA database and the abundance ratio of TIICs was obtained. Kaplan-Meier analysis and Cox regression analysis were used to identify prognostic TIICs. EEA samples were grouped according to the risk score in Cox regression model. Differential analysis and functional enrichment analyses were performed on high- and low-risk groups to find survival-related hub genes, which were verified by Tumor Immune Estimation Resource (TIMER). Result: Four TIICs including memory CD4+ T cells, regulatory T cells, natural killer cells and dendritic cells were identified. And two hub gene modules were found, in which 6 hub genes including APOL1, CCL17, RBP4, KRT15, KRT71 and KRT79 were significantly related to overall survival and were closely correlated with some certain TIICs in the validation of TIMER. Conclusion: In this study, 4 prognostic TIICs and 6 hub genes were found to be closely related to EEA. These findings provided new potential targets for EEA immunotherapy.